Gilbert's syndrome targeted therapy - O.M. Вabadzhanian; O.V. Shutova; L.G. Voloshyna; O.B. Hanzii; Abbas Kaafarani; O.L. Slobodianiuk (Zaslavsky O.Yu., 2017)
The article presents the diagnostic criteria and clinical features of Gilbert's syndrome. The results of clinical studies and observations on the use of ursodeoxycholic acid preparation for targeted therapy of children with Gilbert's syndrome were considered.